Sistem Pendukung Keputusan Pemilihan Media Cetak Sebagai Sarana Promosi Menggunakan Metode Analytical Hierarchy Process Dan Weighted Product - Gunawan Gunawan (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2019)
The selection of advertising media in the development and business competition is very important. It determines that criteria and the alternative for each person is different. It makes decisions are very difficult because we have a lot of choices, time and cost.Decisions that are fast and appropriate in determining the best print media as a promotion, which is in accordance with the needs and desires of the advertiser.Selection of Analytical Hierarchy and Weighted Product (WP) method as a tool to assist in making decisions with calculations done by using AHP to get criteria weight and continue using the WP method. Both methods can provide recommendations in the selection of print media as a medium of promotion. The result of combining the two methods results in a rankingKeywords : Analytical Hierarchy Process Weighted Product, media print